The interplay between oil and food commodity prices: has it changed over time? - Peersman, Gert; Rüth, Sebastian; Van der Veken, Wouter (Discussion paper series, 2019)
Using time-varying BVARs, we find that oil price increases caused by oil supply shocks did not affect food commodity prices before the start of the millennium, but had positive spillover effects in more recent periods. Likewise, shortfalls in global food commodity supply - resulting from bad harvests - have positive effects on crude oil prices since the early 2000s, in contrast to the preceding era. Remarkably, we also document greater spillover effects of both supply shocks on metals and minerals commodity prices in recent periods, as well as a stronger impact on the own price compared to earlier decades. This (simultaneous) time variation of commodity price dynamics cannot be explained by the biofuels revolution and is more likely the consequence of heightened informational frictions and information discovery in more globalized and financialized commodity markets.
Keywords: Graue Literatur